2007
DOI: 10.1002/chem.200601860
|View full text |Cite|
|
Sign up to set email alerts
|

2,4,5‐Trinitroimidazole‐Based Energetic Salts

Abstract: Hetero Diels‐Alder (HDA) cycloaddition – as an effective modular conjugation approach – is employed to graft thioamide endfunctional oligopeptides onto solid cyclopentadienyl (Cp) functional cellulose substrates generating cellulose‐peptide hybrid materials. The highly reactive Cp moieties serve as diene functionality in the consecutive HDA reaction on the biosubstrate surface. Oligopeptides (i.e., the model peptide Gly‐Gly‐Arg‐Phe‐Pro‐Trp‐Trp‐Gly and the antimicrobial peptide tritrpticin) are functionalized a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
51
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(52 citation statements)
references
References 59 publications
1
51
0
Order By: Relevance
“…Nevertheless, its barium salt has good solubility in water. Thus, energetic salts 5-9 were readily synthesized by metathesis reactions of BaA C H T U N G T R E N N U N G (TNF) 2 formed in situ with one equivalent of the corresponding sulfate salt (Scheme 1). All of the prepared energetic salts proved to be stable in air and could be stored for extended periods.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, its barium salt has good solubility in water. Thus, energetic salts 5-9 were readily synthesized by metathesis reactions of BaA C H T U N G T R E N N U N G (TNF) 2 formed in situ with one equivalent of the corresponding sulfate salt (Scheme 1). All of the prepared energetic salts proved to be stable in air and could be stored for extended periods.…”
Section: Resultsmentioning
confidence: 99%
“…[7] Since some organic anions have considerable nitrogen content and are expected to have attractive stabilities toward friction, impact, and heat, they are also good candidates for energetic salt design, e.g., 5,5′-azotetrazolate, [8] 3,5-dinitro-1,2,4-triazolate, [9] 4,5-dinitroimidazolate, [9] 3-nitro-triazolate, [10] 5-nitro-tetrazolate, [10,11] iminobis(5-tetrazolate), [8c] 5′-bis(tetrazolate), [8c] bisdinitroimidazolate, [12] 3-nitro-1,2,4-triazol-5-one, [13] picrate, [14] 3-amino-6-nitroamino-tetrazine anion, [15] and trinitroimidazole. [16] Recently, copper complexes of N,N-bis-(1 (2)H-tetrazol-5-yl)amine (H 2 Bta) (1) were reported. [17] The acidic protons of H 2 Bta enable the formation of the corresponding salts by reactions with nitrogen-rich bases.…”
mentioning
confidence: 99%
“…Besides, materials comprising structure of azole rings always show a better oxygen balance property in plenty of practical test. [14,[16][17][18][19] Among most of the energetic compounds, 1,2,4-triazole and its derivatives are very promising because of both theoretical and practical prospect. Shreeve, Klapötke, and others researchers have found that they have good physical and chemical performances, as well as excellent environmental compatibility, compared to other compounds.…”
Section: Introductionmentioning
confidence: 99%